2015
DOI: 10.1371/journal.pone.0116216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mobile Phones and Factors Influencing Usage by Caregivers of Young Children in Daily Life and for Health Care in Rural China: A Mixed Methods Study

Abstract: IntroductionTo capitalise on mHealth, we need to understand the use of mobile phones both in daily life and for health care.ObjectiveTo assess the prevalence and factors that influence usage of mobile phones by caregivers of young children.Materials and MethodsA mixed methods approach was used, whereby a survey (N=1854) and semi-structured interviews (N=17) were conducted concurrently. The quantitative and qualitative data obtained were compared and integrated. Participants were caregivers of young children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Nearly all studies have found positive effectiveness of mobile or smartphone applications (apps) for health management [32, 33]. One review also confirmed that mobile technology interventions significantly improved an array of health care outcomes in Chinese populations [3437]. Similarly, social networks such as Facebook, Twitter, YouTube, and WeChat provide new indexes in building relationships, finding and sharing information, and working co-operatively with others [38].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all studies have found positive effectiveness of mobile or smartphone applications (apps) for health management [32, 33]. One review also confirmed that mobile technology interventions significantly improved an array of health care outcomes in Chinese populations [3437]. Similarly, social networks such as Facebook, Twitter, YouTube, and WeChat provide new indexes in building relationships, finding and sharing information, and working co-operatively with others [38].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a high number of mobile phone users use it primarily for calling and receiving calls, while a small proportion of users use it for text messaging (Michelle et al, 2015). Most of the time text messages are not read if they are too many, perceived as unimportant, constitute junks and may be embarrassing, hence they are deleted (Patrick et al 2013 andMichelle et al, 2015).…”
Section: Limitations Of Sms Interventionsmentioning
confidence: 99%
“…This shows that mobile phone has the potential to support medications regimens and immunization uptakes. Research has also shown that the most frequently used mobile phone functions are calls and text messages (Michelle, et al 2015, Dick et al 2011. Modern functions like web browsing, chat, media and television do not cut across all mobile phone platforms (Tran and Houston 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations